INTERNALLY GENERATED REVENUE (IGR) AND CORRUPTION IN NIGERIA: A FOCUS ON TAXES AND RATES - OWENVBIUGIE VINCENT OVENSERI (International Studies Journal)
This study investigates the pervasive impact of corruption on Internally Generated Revenue (IGR) in Nigeria, focusing specifically on the collection and administration of taxes and property rates. Utilizing a quantitative research design, data were collected through a structured questionnaire administered to 162 respondents in Edo State, representing various demographics and socioeconomic backgrounds. The analysis reveals a significant negative correlation between corruption and tax collection efficiency, evidenced by a correlation coefficient of -0.65. The findings indicate that high levels of bribery, embezzlement, and misappropriation of funds among tax and revenue officials substantially hinder effective revenue generation, thereby limiting the financial resources available for public services and infrastructural development. Moreover, the study highlights that corruption not only constrains revenue collection but also erodes public trust in government institutions, leading to a diminished perception of the efficacy and reliability of public services. This erosion of trust has far-reaching implications for governance and accountability in Nigeria, as citizens become increasingly disillusioned with their government’s ability to manage resources effectively. To address these challenges, the study emphasizes the urgent need for enhanced transparency, robust accountability mechanisms, and the strengthening of institutional frameworks to combat corruption effectively. Policymakers are urged to implement reforms aimed at improving revenue administration and ensuring that collected taxes and rates are utilized for the public good. By contributing valuable insights to the existing literature on public finance management, this research serves as a critical resource for policymakers and stakeholders seeking to enhance revenue generation while curbing corrupt practices in Nigeria.